2020
DOI: 10.3390/nano10091887
|View full text |Cite
|
Sign up to set email alerts
|

Ta Doping Effect on Structural and Optical Properties of InTe Thin Films

Abstract: The objective of this work was to study the influence of Ta doping on the structural, transmittance properties, linear absorption parameter, and nonlinear absorption properties of InTe thin films. The as-deposited samples with different Ta doping concentrations were prepared by a magnetron co-sputtering technique and then annealed in nitrogen atmosphere. Structural investigations by X-ray diffraction revealed the tetragonal structure of InTe samples and that the crystallinity decreases with increasing Ta dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The σ TPA of 4 L-Bi 2 S 3 is 1.32 × 10 3 GM. These values are 1–2 orders of magnitude higher than InTe (89.42 ± 0.05 GM) . Meanwhile, the value is comparable to CdSe quantum dots (∼10 3 GM) but lower than that of MAPbBr 3 microcrystals (∼10 4 GM) due to the larger molecular density of chalcogenide compounds.…”
Section: Resultsmentioning
confidence: 77%
“…The σ TPA of 4 L-Bi 2 S 3 is 1.32 × 10 3 GM. These values are 1–2 orders of magnitude higher than InTe (89.42 ± 0.05 GM) . Meanwhile, the value is comparable to CdSe quantum dots (∼10 3 GM) but lower than that of MAPbBr 3 microcrystals (∼10 4 GM) due to the larger molecular density of chalcogenide compounds.…”
Section: Resultsmentioning
confidence: 77%
“…investigated the transmittance of the Ta‐doped InTe thin films and they reported that the transmittance is nearly 84% in the transparence region and the value of transmittance increases after Ta doping. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…C. Liu et al investigated the transmittance of the Ta-doped InTe thin films and they reported that the transmittance is nearly 84% in the transparence region and the value of transmittance increases after Ta doping. [32] The optical bandgap of the pure CdS semiconductor thin films was calculated as 2.14 eV. Optical bandgap values of 0.06 and 0.1 m boron-doped CdS semiconductor thin films were found to be 2.51, and 2.43 eV respectively.…”
Section: Absorbance Transmittance and Optical Bandgapmentioning
confidence: 93%
“…The splitting of the conduction band promotes a decrease in optical adsorption due to transitions between its levels. A strong dispersion of the s-level of the conduction band, which is characteristic of most transparent conducting oxides, leads to a shift of the optical absorption edge towards higher energies with an increase in the concentration of charge carriers [34][35][36][37]. The filling of the dispersive conduction band leads to an increase in the energy required for the transition of an electron from the valence band to the conduction band (Figure 13).…”
Section: Influence Of the Chemical Parameters Of Film-forming Solutio...mentioning
confidence: 99%